Sabbath and sectarianism in seventeenth-century England - Katz, David S.,Kaṣ, Dāwid Ben-Šāʾûl (Brill, 1988)
This book is a study of the pratical application of a religious idea: the belief in the continuing validity of the Old Testament, especially the Ten Commandments, which ordained the observance of the Sabbath on the seventh day, Saturday. The author traces the growth and development of the most radical of English Sabbath observers, those who revered the Jewish Sabbath in a Christian context. But this is not only a pre-history of the Seventh-Day Adventists. It is also the story of the remarkable persistence of a revolutionary religious belief powerful and convincing enough to survive the Restoration and continue into modern times. The Saturday-Sabbath gradually became institutionalized in a nonconformist sect in which the ideological foundation was sufficient to unite men who on political grounds should have been the most bitter of enemies, including Fifth Monarchists, millenarians, neutrals, and Royalists alike. That those men and their followers could amicably join forces after the Restoration is testimony to the power of religious ideas which might overshadow the political affiliations of the civil war.
Keywords: England; Sabbat; Puritanismus; Geschichte; USA; Geschichte 1570-1750; Sabbatarier